Communication Pattern Between People Who’s Manyanda With Family Members Who’s Disanda - Hasmira, Mira Hasti (Science and Environmental Journal for Postgraduate, 2018)
Nagari Talang was a village that located around of Mount Talang, Gunung Talang District, Solok Regency, West Sumatra. Nagari Talang was rich with unique and interesting tradition included in tradition of death. Manyanda is replacing the function of people who have died as a socially with people who are still alive. Manyanda was also intended to help the family left behind so that they do not feel so sad. This study described how the pattern of communication between people who was manyanda with family members who is disanda. This research is an ethnographic study of communication. Based on research conducted, there were two patterns of communication. This communication pattern was divided based on the level of community understanding about manyanda. In groups of people who understand the tradition of widow well, the communication pattern was two-way and lasts for quite a long time. Whereas in the community group that only understands manyanda as a adherence to tradition, the communication pattern tends to run in one direction and lasts a short period of time, at most two years.